Bestrophin-3 Expression in a Subpopulation of Astrocytes in the Neonatal Brain After Hypoxic-Ischemic Injury - Golubinskaya, Veronika; Vontell, Regina; Supramaniam, Veena; Wyatt-Ashmead, Josephine; Gustafsson, Helena; Mallard, Carina; Nilsson, Holger (Frontiers in Physiology, 2019)
Bestrophin-3, a potential candidate for a calcium-activated chloride channel, recently was suggested to have cell-protective functions. We studied the expression and alternative splicing of bestrophin-3 in neonatal mouse brain and after hypoxic-ischemic (HI) injury and in human neonatal brain samples. HI brain injury was induced in 9-day old mice by unilateral permanent common carotid artery occlusion in combination with exposure to 10% oxygen for 50 min. Endoplasmic reticulum stress was induced by thapsigargin treatment in primary culture of mouse brain astrocytes. We also investigated expression of bestrophin-3 protein in a sample of human neonatal brain tissue. Bestrophin-3 protein expression was detected with immunohistochemical methods and western blot; mRNA expression and splicing were analysed by RT-PCR. HI induced a brain tissue infarct and a pronounced increase in the endoplasmic reticulum-associated marker CHOP. Three days after HI a population of astrocytes co-expressed bestrophin-3 and nestin in a penumbra-like area of the injured hemisphere. However, total levels of Bestrophin-3 protein in mouse cortex were reduced after injury. Mouse astrocytes in primary culture also expressed bestrophin-3 protein, the amount of which was reduced by endoplasmic reticulum stress. Bestrophin-3 protein was detected as well in astrocytes in the hippocampal region of the human neonatal brain which had patchy white matter gliosis and neuronal loss in the Sommer’s sector of the Ammon’s horn (CA1). Analysis of bestrophin-3 mRNA in mouse brain with and without injury showed the presence of two truncated spliced variants, but no full-length mRNA. Total amount of bestrophin-3 mRNA increased after HI, but did not show an injury-related change. However, the splice variants of bestrophin-3 mRNA were differentially regulated after HI depending on the presence of tissue injury. Our results show that bestrophin-3 is expressed in neonatal mouse brain after injury and in the human neonatal brain with injury. In mouse brain bestrophin-3 protein is upregulated in a specific astrocyte population after injury and is co-expressed with nestin. Splice variants of bestrophin-3 mRNA respond differently to HI, which might indicate their different roles in tissue injury.